NASM essentials of personel fitness training - Clark, Micheal; Sutton, Brian G.; Lucett, Scott (Jones & Bartlett Learning, 2012)
This text is a recommended resource for the NASM Certified Personal Trainer (CPT) certification. The NASM CPT certification is accredited by the National Commission for Certifying Agencies (NCCA). Since 1987, the National Academy of Sports Medicine (NASM) has been a global leader in providing evidence-based certifications and advanced credentials to health and fitness professionals. NASM Essentials of Personal Fitness Training, Fourth Edition Revised, continues to lead the way by providing the most comprehensive resource for aspiring personal trainers and other health and fitness professionals. Based on NASM's proprietary Optimum Performance Training (OPT) model, you will learn a systematic approach to program design with exercise program guidelines and variables; protocols for building stabilization, strength, and power programs; guidance on how to build a clientele through professional development; and more! By following the techniques in this book, you will gain the information, insight, and inspiration you need to change the world as a health and fitness professional. Key Features: Two new chapters: Exercise Metabolism and Bioenergetics and Introduction to Exercise Modalities